Could seasonal Influenza virus vaccine reduce the risk and severity Of SARS-CoV-2 infection? - The first Egyptian experience - Dina Ali; Khaled Raafat (Microbes and Infectious Diseases, 2022)
Background: Coronavirus Disease 2019 (COVID-19) is a serious public health issue worldwide. A safe and effective COVID-19 vaccine is a crucial measure to control the current pandemic. Many efforts have been devoted to the development of COVID-19 vaccines. However, the mistrust of COVID-19 vaccines has a negative impact on the willingness to receive the vaccine. Because of the cross-reactivity between influenza and coronaviruses, influenza immunization may be useful in preventing COVID-19 infection. Aim: Assessing the association between seasonal influenza virus vaccination and the acquisition and severity of COVID-19 in Egyptian individuals. Methods: This was an observational retrospective cohort study that included sixty participants who were classified into two equal groups based on their influenza virus vaccination status (vaccinated or not). The primary outcome was the susceptibility to COVID-19 infection and the secondary outcome was the severity of COVID-19 symptoms. Results: Among the unvaccinated group (n=17/30, 56.7%) had a COVID-19 infection compared to (n=8/30, 26.7%) in the vaccinated group (p < /em> value =0.02). The calculated OR was 3.6. Regarding the severity of COVID-19 infection, 11 individuals in the unvaccinated group (n=11/17, 64.7%) developed mild infection, (n=5/17, 29.4%) got moderate illness and (n=1/17, 5.9%) developed severe disease whereas (n=6/8, 75%) individuals in the vaccinated group had mild infection and (n=2/8, 25%) developed illness of moderate intensity (p < /em> value =0.7). Conclusion: Seasonal influenza virus vaccine seems to have a protective role against the acquisition of COVID-19 infection but does not reduce the severity of the disease.